TEACHING ENGLISH AS A FOREIGN LANGUAGE: A CASE STUDY FROM POLAND - ROMANIUK, JAROSLAW R.; MILLER, KRISTIN; PIESKI, MARY KAY; WOJCIK, TERESA G.; FARKAS, KATHLEEN J. (Society Register, 2020)
This article presents a detailed history of the development of a particular immersion program to teach English to young Polish students. The program draws support from two organizations, the Kościuszko Foundation and the Polish Scouting Organization. Kościuszko Foundation is dedicated to strengthening the ties between the United States and Poland as well as to increase knowledge of Poland’s history and culture in the United States. The cooperation of these two organizations developed an experience of immersion in language and cultural exchange. Both the teachers and the students in this program benefited from the opportunity to engage in a number of different types of language activities and cultural events through a summer camp experience. This program is, of course, unique, but the elements of context, culture and immersion could be used in other programs to develop English skills and knowledge in the context American culture.